2018
DOI: 10.1155/2018/6934809
|View full text |Cite
|
Sign up to set email alerts
|

The Ethanol Supernatant Extracts of Liushenwan Could Alleviate Nanodiethylnitrosamine-Induced Liver Cancer in Mice

Abstract: Liver cancer is one of the leading causes of cancerous deaths worldwide. At present, the treatment of hepatocellular carcinoma (HCC) remains to be a problem globally. Liushenwan (LSW), an ancient Chinese medicine previously used to treat localized infections, was recently reported to possess anticancer activity. Here in this study, we aim to examine the effect of LSW-ET (LSW-ET is the supernatant fraction of LSW from ultrasound assisted ethanol extraction) in prevention and treatment on nanodiethylnitrosamine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…It has been found that activation of the Wnt/b-catenin signaling drives liver cancer formation and that b-catenin expression is abnormal in the majority of human liver cancer samples (34,39). In previous studies, we confirmed the relationship of the b-catenin/COX-2 ring (40). Elevated b-catenin expression and nucleation promote COX-2 expression, and elevated COX-2 expression, in turn, promotes b-catenin expression, HMGB1 is located downstream of the b-catenin/COX-2 loop, and elevated expression of b-catenin and COX-2 promotes HMGB1 expression (40,41).…”
Section: Discussionsupporting
confidence: 78%
“…It has been found that activation of the Wnt/b-catenin signaling drives liver cancer formation and that b-catenin expression is abnormal in the majority of human liver cancer samples (34,39). In previous studies, we confirmed the relationship of the b-catenin/COX-2 ring (40). Elevated b-catenin expression and nucleation promote COX-2 expression, and elevated COX-2 expression, in turn, promotes b-catenin expression, HMGB1 is located downstream of the b-catenin/COX-2 loop, and elevated expression of b-catenin and COX-2 promotes HMGB1 expression (40,41).…”
Section: Discussionsupporting
confidence: 78%
“…In previous studies, we have confirmed that the main components in LSW-ET include telocinobufagin, bufotaline, cinobufotalin, bufalin, cinobufagin, and resibufogenin, most of them have anticancer activity (Chen et al, 2018). We separated the components of LSW-ET and Nano-LSW using HPLC, and determined the content of their main components.…”
Section: Component Analysis Of Nano-lswsupporting
confidence: 54%
“…Therefore, the study of high-efficiency liver cancer treatment drugs that exhibit low (or no) toxicity is crucial (Dhanasekaran et al, 2010). It has been reported that the alcohol extracted portion of LSW-ET is the main effective portion of LSW against tumors (Chen et al, 2018). However, LSW contains realgar and venenum bufonis, whichh has been queried for its safety (Zhang et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations